The molecular dynamics simulation studies of nanoscale mechanical deformation behaviors and mechanisms in metallic glasses - Tang, Chao (2017)
As a new class of materials, metallic glasses (MGs) appear to have great potential for engineering applications, due to their superior properties including high strength, good corrosion resistance, thermoformability etc. Despite several attractive traits of MGs, the main drawback lies in their limited ductility at room temperature. Typically, the topological and chemical short-to-medium range structure is believed to be intimately linked with the physical and mechanical properties of MGs, and hence becomes one of the fundamental interests in this endeavor. In this regard, the main objective of this PhD project is to examine the structure-property relationships in MGs by using molecular dynamics (MD) simulations.